Formulasi dan Uji Penetrasi In Vitro Sediaan Gel Sistem FitosomEkstrak Buah Asam Jawa (Tamarindus indica L.) - Devina Chandra; Cut Masyithah Thaib; Steven Tandiono; Manuppak Irianto Tampubolon (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Tamarind fruit extract (Tamarindus indica L.) contained flavonoids such as quercetin as antioxidants. The hydrophilic nature of tamarind fruit (Tamarindus indica L.) led to poor penetration and low bioavailability. Research was conducted to address penetration issues by preparing a phytosome drug delivery system incorporated into tamarind fruit extract formulations. The study aimed to formulate a tamarind fruit extract gel with phytosome preparation to enhance the effectiveness of active ingredient penetration. Phytosome preparation was carried out using the thin layer hydration method with concentrations of 1.5%, 3%, and 4.5%. Evaluation of the gel preparations showed that the color of FI (1.5%) was yellowish-brown, F2 (3%) was light brown, and F3 (4.5%) was dark brown. All formulations had a distinctive odor, pH ranged from 4.3 to 5.2, viscosity ranged from 4,333 to 7,500 cPs, spreadability ranged from 5.2 to 5.8 cm, and they had good stability, were homogeneous, and did not cause irritation. Penetration tests using Franz diffusion cells were performed on male rabbit skin (Oryctolagus cuniculus). The penetration results were analyzed using UV-Vis spectrophotometry with a maximum wavelength of 435 nm. The cumulative amount penetrated was 13.2085 ppm for F1 (1.5%), 14.2142 ppm for F2 (3%), and 15.5136 ppm for F3 (4.5%). In contrast, the tamarind fruit extract gel without phytosomes had a cumulative penetration amount of 1.3684 ppm. The tamarind fruit extract's phytosome gel showed better penetration than the tamarind fruit extract gel without phytosomes.